Ibuprofen lacks direct antimicrobial properties for the treatment of urinary tract infection isolates. Issue 8 (11th June 2019) - Whiteside, Samantha A.; Dave, Sumit; Reid, Gregor; Burton, Jeremy P.
Abstract : The high incidence of urinary tract infection (UTI) among women and children, in combination with a lack of antibiotic efficacy with regard to pathogen eradication and recurrence prevention, as well as the negative side effects associated with antibiotics, has led researchers to explore the role of non-steroidal anti-inflammatory drugs as a primary management strategy. The aim of this study was to determine whether ibuprofen (IBU) or one of its major metabolites, 2-carboxyibuprofen (CIBU), could affect the growth and adhesion of the two most common uropathogens, Escherichia coli and Enterococcus faecalis . The bacterial growth and adhesion to the urothelial cells of E. coli UTI89 and E. faecalis 1131 in the presence of physiologically relevant concentrations of IBU and CIBU were assessed. The effect of IBU on bacterial adhesion to urothelial cells was also assessed following exposure to trimethoprim/sulfamethoxazole (TMP/SMX) and nitrofurantoin. Bacterial growth was not affected by IBU. Further, only at high levels of IBU not regularly found in the bladder was there a significant increase in E. faecalis 1131 attachment at growth inhibitory concentrations of TMP/SMX. There was no effect on the attachment of E. faecalis or E. coli to urothelial cells in the presence of nitrofurantoin. These studies indicate that the beneficial effects of IBU for UTI management are likely mediated through its anti-inflammatory properties rather than direct interactions with uropathogens in the bladder.